Um estudo da gênese das dynamic capabilities: o caso da tecnologia bancária no Brasil - Kassab, Cláudio (2011)
The perspective of Dynamic Capabilities is often used in a context of institutional stability. This master thesis analyzes the development of this theoretical perspective in a context of political and economic instability, which is the case of the Brazilian economy from the mid-1960s to the mid-1990s. This study utilizes a historical and procedural approach to investigate the emergence of Dynamic Capabilities in the Brazilian banking sector during the period studied. An analytical framework is built based on the Dynamic Capabilities perspective and on the Resource-and Knowledge-Based Views. Data sources are statements taken from the book “Tecnologia bancária no Brasil: uma história de conquistas, uma visão de futuro” (FONSECA; MEIRELLES; DINIZ, 2010) and interviews with key actors. The statements show that the massive investments in banking technology started after a big financial reform that happened in 1964, and that the following years can be divided in periods of approximately one decade that presented certain institutional characteristics. As the conditions changed in each period, the banks also changed the way they worked with Information Technology. At first, ad hoc projects were executed under the direct command of the leaders of the banks. Over time, as technology became more complex, the technological infrastructure grew and institutional instabilities happened, Brazilian banks increasingly developed partnerships among themselves and with local suppliers, decentralized technology area, became more flexible, strengthened corporate governance and increasingly adopted routines to take care of Information Technolgy, which led to the gradual development of microfoundations of Dynamic Capabilties along these periods. In the mid-1990s, Brazil achieved institutional stabilization and opened the economy to foreign competition, and thus the country had the conditions that the adopted theoretical approach considers ideal for the Dynamic Capabilities to become sources of competitive advantage. Brazilian banks have shown themselves ready to face this new phase, which is an evidence that they had developed Dynamic Capabilities in previous decades, and part of that development could be attributed to the institutional instabilities that they had faced in that period.